Electrically Bloomed Platinum Nanoflowers on Exfoliated Graphene: An Efficient Alcohol Oxidation Catalyst. Issue 10 (1st January 2016) - Zhang, Zishuai; Lopes, Joao Henrique; Ye, Siyu; Gostick, Jeff T.; Barralet, Jake E; Merle, Geraldine
Abstract : Platinum (Pt) based electrocatalysts have electrochemical performance that outperforms many other noble metal and metal oxide based materials. Increasing performance allows a reduction in the platinum load, and thus reduce the cost of various devices such as fuel cells. A double pulse electrochemical approach was developed to nucleate and grow Pt nanoparticles into flower shaped assemblies on graphene sheets. The unique morphology and structure of the Pt were characterized by field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM). The electrocatalytical activities of the Pt nanoflowers were evaluated using methanol and ethanol oxidation as model reactions. This proposed method has led to the synthesis of Pt nanoflowers with the ability to control, both their density and their size on defect free graphene.